A Multilayer Interactome Network Constructed in a Forest Poplar Population Mediates the Pleiotropic Control of Complex Traits - Gong, Huiying; Zhu, Sheng; Zhu, Xuli; Fang, Qing; Zhang, Xiao-Yu; Wu, Rongling (Frontiers in Genetics, 2021)
The effects of genes are interrelated and interdependent, through physiological and biochemical processes, it is common for genes to express pleiotropic control on complex traits. However, the study of gene expression and participating pathway in vivo at the whole-genome level is challenging. Here, we develop a coupled regulatory interaction differential equation to obtain genetic effects and independent genetic effects of trait growth. Based on the evolutionary game theory and developmental modularity theory, we construct multilayer omnigenic networks of bidirectional, signed, and weighted epistatic interactions, which are divided into metagalactic networks, intergalactic networks and local interstellar networks to describe layers of structure between modules, submodules and individual SNPs. Through the multilayer interactome networks, we can explore the genetic complexities of how genes interact with each other and analyzes not only differentiated expression of QTLs, but also previously uncharacterized determinant SNPs, which are negatively regulated by other SNPs based on effects decomposition. Our research framework provides a tool to comprehend the pleiotropic control of complex traits and explore the inherent directional connections of genes structure within omnigenic networks.